1997
DOI: 10.1046/j.1365-3148.1997.d01-43.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell salvage auto transfusion in total knee replacement surgery

Abstract: We conducted a prospective, randomized study to assess the impact of cell salvage, auto transfusion on the requirements for allogeneic blood for patients undergoing a total knee replacement (TKR). One hundred consecutive TKR patients were randomly allocated to receive either autologous blood (using cell salvage) or an allogeneic blood transfusion as necessary. Patients allocated to the autologous group were rescued with allogeneic blood if the postoperative haemoglobin fell below 9 g dL-1. Forty-two (84%) of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 3 publications
2
42
1
3
Order By: Relevance
“…The use of cell salvage in combination with a leukocyte depletion filter appears to be safe in for obstetric use and in cases of malignancy. It has been demonstrated that cell salvage reduces the need for allogeneic blood transfusion in revision hip [3] and knee replacement surgery [10,11]. The only absolute contraindication to the use of cell salvage and autologous blood transfusion is patient refusal [2].…”
Section: Discussionmentioning
confidence: 99%
“…The use of cell salvage in combination with a leukocyte depletion filter appears to be safe in for obstetric use and in cases of malignancy. It has been demonstrated that cell salvage reduces the need for allogeneic blood transfusion in revision hip [3] and knee replacement surgery [10,11]. The only absolute contraindication to the use of cell salvage and autologous blood transfusion is patient refusal [2].…”
Section: Discussionmentioning
confidence: 99%
“…We have been using intraoperative red cell salvage for primary and revision TKA, with success in reducing allogenic transfusion requirement (Dan M, Unpublished Data). The efficacy of cell salvage in TKA in our cohort compared to previously published studies353637) is outlined in Table 3. We concluded perioperative red cell salvage reduces but does not eliminate the need for allogenic blood.…”
Section: Intraoperative Strategiesmentioning
confidence: 99%
“…An audit of our transfusion rates in comparison to other studies in the literature is listed in table 3 for THA [32,33,34] and table 4 for TKA. [35,36,37] Peri-operative red cell salvage definitely reduces but does not eliminate the need for allogenic blood, especially in patients who have a low baseline haemaglobin pre-operatively.…”
Section: Intra-operative Strategiesmentioning
confidence: 99%